1982
DOI: 10.1159/000123386
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Evidence that Serotonergic Stimulation of Prolactin Secretion is Mediated via the Dorsal Raphe Nucleus

Abstract: Administration of the serotonin-releasing drug DL-p-chloroamphetamine (PCA) to rats caused a dose-dependent increase in plasma prolactin levels. The effect was maximal 2 h after administration. The effect of PCA was prevented by prior administration of the serotonin synthesis inhibitor p-chlorophenylalanine-methyl ester (PCPA). PCPA pre-treatment did not prevent the increase in plasma prolactin levels after administration of the serotonin agonist quipazine which is consistent with a postsynaptic receptor inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

1984
1984
1999
1999

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(42 citation statements)
references
References 31 publications
1
40
0
1
Order By: Relevance
“…The average serum prolactin levels (ng/ml) after P implantation (days [15][16][17][18][19][20][21][22][23][24][25][26][27][28] in all of the monkeys whose pontine tissue blocks were used in this study equaled 35.6 ± 1.6 in the spayed group, 31.7 ± 3.6 in the E-treated group, and 120.4 ± 13.5 in the E+P-treated group. Only the E+P treatment caused a significant increase in serum prolactin (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average serum prolactin levels (ng/ml) after P implantation (days [15][16][17][18][19][20][21][22][23][24][25][26][27][28] in all of the monkeys whose pontine tissue blocks were used in this study equaled 35.6 ± 1.6 in the spayed group, 31.7 ± 3.6 in the E-treated group, and 120.4 ± 13.5 in the E+P-treated group. Only the E+P treatment caused a significant increase in serum prolactin (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, serotonin antag onists for 5HT-lb receptors block prolactin secretion pro moted by administration of a serotonin releaser, fenflur amine [ 14], or by 5HT agonists [15]. Finally, lesion of the dorsal raphe in rats abolishes prolactin release induced by pretreatment with the serotonin releaser, PCA [16], and produces supersensitivity in the prolactin dose response to the 5HT agonist, RU24969 [17].…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, the fact that both CRT and PRL mean plasma levels were greater in high-IT depressed patients than in low-IT depressed patients, during pre-clonidine pe riods, suggests the stimulating role that the serotonergic system might play in releasing these hypothalamic factors in the former group. In effect, it is a well-known fact that the central serotonergic system is involved in the releasing of corticotrophin-releasing hormone and triggers PRLreleasing mechanisms [3,9,20,22,24,25,31]. Furthermore, the proven fact that fenfluramine (a serotonin depletor agent) [10] is able to induce a quick improvement of high-IT depressed patients [18] provides additional reinforcement to this presumption.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the release of both 5-HT and DA can be stimulated by PCA may explain the delayed response of PRL (at 60 min only) and the inconsistency between ME DOPAC/5-HIAA and serum PRL levels. An earlier study suggested that PCAinduced PRL release appears to be mediated by increased 5-HT release since prior depletion of central 5-HT prevents PCA's effect [37]. Nevertheless, the PCA-induced PRL secretion should be the net effect of 5-HT, 5-HTstimulated PRF, and DA.…”
Section: Effects Of Pcpamentioning
confidence: 98%